Eye donation: awareness and willingness among shopkeepers - Patil, Reshma; Gothankar, Jayashree; Bhat, Prerna; Saluja, Jitesh; Sane, Shrivallabh (International Journal Of Community Medicine And Public Health, 2017)
Background: Corneal blindness is one of the important causes of blindness in India that can be conventionally cured by corneal transplantation. The number of corneal transplants done is less than the actual requirement in India due to inadequate number of corneas collected. Therefore increasing awareness regarding eye donation and also willingness to pledge for the same is the today’s need. Hence current study was undertaken to assess the awareness regarding eye donation and the willingness to pledge the eye for donation amongst the shopkeepers in urban area of Pune city. Methods: Total 1014 shopkeepers above 15 years of age from field practice area of Urban Health Training Center of a private medical college, Pune were interviewed regarding awareness of eye donation and willingness to pledge eye for eye donation. Results: Out of total 1014 subjects, 752 (74.16%) were aware of eye donation amongst which males were maximum (75.13%) compared to females (24.87%). Awareness was more in the age group >40 years i.e. 47.87%. Willingness to pledge eyes for eye donation was 19.83%. Conclusions: Though the awareness regarding eye donation is high very few of them are ready to donate their eyes. Therefore more transfer of knowledge is needed to motivate people for eye donation which will be helpful in reducing the gap between the availability of corneas and actual requirement.